A Review On : To Develop and Validate Analytical Method for Determination of Methimazole in Bulk and Pharmaceutical Dosage Form (International Journal of Scientific Research in Science and Technology, 2024)
Hyperthyroidism is a condition characterized by increased in synthesis and secretion of thyroid hormones from thyroid gland. Methimazole is an anti-hyperthyroidism drug. It is of great importance and significance for life science. Up to now, various different methods have been applied for the determination of methimazole, such as spectrophotometry1-3, LC4, HPLC6, RP-HPLC7, HPLC-UV8, electrochemical analysis9, kinetic method10. In this paper, a new UV-Spectrophotometric method for the determination of methimazole has been established. The chemical name of Methimazole is (1-methylimidazole-2-thiol). The chemical formula of Methimazole is C4H6N2S and the molecular weight is 114.17 g/mol. The structure of Methimazole features a 5 membered imidazole ring with a methyl group at position 1st and thione group at position 2nd. Methimazole is white colour powder and has melting point 1440 C.